2006
DOI: 10.1111/j.1468-2508.2006.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

The Political Conditioning of Economic Perceptions

Abstract: Economic theories of voting argue that party popularity and vote are heavily influenced by the performance of the economy. Inferences about the direction of causality between perceptions of the economy and party support remain questionable, however. This article evaluates the microfoundations of economic theories of voting and party popularity using multiwave panel data. We model the dynamic relationships between party support and retrospective economic perceptions-both sociotropic and egocentric-through the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
301
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(323 citation statements)
references
References 62 publications
10
301
2
2
Order By: Relevance
“…In particular, he saw sociotropic retrospective items as error-laden, with respondents in the same survey exhibiting widespread disagreement over the condition of the national economy. Part of this error could come from partisan bias for or against the incumbent party (Evans and Andersen, 2006), and another part from general misinformation (Anderson, 2007: 280).…”
Section: Literature and Theorymentioning
confidence: 99%
“…In particular, he saw sociotropic retrospective items as error-laden, with respondents in the same survey exhibiting widespread disagreement over the condition of the national economy. Part of this error could come from partisan bias for or against the incumbent party (Evans and Andersen, 2006), and another part from general misinformation (Anderson, 2007: 280).…”
Section: Literature and Theorymentioning
confidence: 99%
“…Algunos académicos han argumentado que las percepciones individuales sobre el estado de la economía nacional podrían ser endógenas a la opción de voto (e.g., Wlezien et al, 1997;Anderson et al, 2004;Evans y Andersen, 2006). Esto es, que un individuo que apoya al candidato del partido de gobierno pueda tener una visión más optimista sobre las condiciones económicas recientes comparado a un individuo que apoya al candidato de la oposición.…”
Section: Segundos Resultadosunclassified
“…Empirical studies, however, have been consistently pointing to the fact that democratic publics are less sophisticated than expected by democratic theorists, and their economic assessments often deviate from macro-economic realities (Borre 1997;Evans 1999). Most importantly, a number of recent works--a revisionist trend in the economic voting literature--have demonstrated that these deviations are systematic, rather than random, in nature (Anderson 2007;Wlezien et al 1997;Anderson et al 2004;Johnston et al 2005;Enns and Anderson 2009;Evans and Andersen 2006;Evans 1999).…”
mentioning
confidence: 99%
“…Partisanship and political ideology are certainly central to this line of argument (Enns and Anderson 2009;Evans and Andersen 2006;Evans 1999). Instead of relying on objective economic indicators, voters view the economy through the prism of partisan lens and assign credit and blame accordingly.…”
mentioning
confidence: 99%
See 1 more Smart Citation